Determinants of Total Factor Productivity in the EU-CEE. The Role of Intangible Assets and Institutional Quality - Pekarčík, Marek; Šafár, Leoš; Taňkošová, Tatiana (Theoretical and Practical Research in Economic Fields; Vol 17 No 1 (2026): TPREF Volume XVII Issue 1(37) March 2026, 2026)
This study investigates the determinants of total factor productivity (TFP) in European Union (EU) countries, with a particular focus on the transition economies of Central and Eastern Europe (EU-CEE). Using a balanced panel dataset for 2013-2019, we apply fixed-effects panel regression with robust standard errors to assess the impact of four key factors intangible asset accumulation, business environment quality, information and communication technologies (ICTs), and knowledge workers on TFP growth. The results demonstrate that investment in intangible assets has a consistent and statistically significant positive effect on TFP across all model specifications. The quality of the business environment also significantly influences productivity, especially in EU-CEE countries, where institutional reforms and regulatory improvements have delayed but lasting effects. ICTs contribute positively to TFP, with a stronger lagged impact in countries where digital infrastructure and absorption capacity are still developing. Conversely, the share of knowledge workers does not show a statistically significant relationship with productivity unless complemented by investments in intangible and organizational capital. The findings confirm that intangible assets and institutional quality are decisive long-term drivers of productivity growth and convergence in the EU. The policy implications highlight the need for sustained support for intangible investment, ICT diffusion, and institutional strengthening to accelerate productivity and narrow regional disparities.